Affecting Factors of Shallots Production Level in Wanasari Sub-District Brebes Regency (Business and Economic Analysis Journal, 2021)
Shallots are vegetables that are included in the staple food classification. Therefore, it should be controlled in order to prevent an economic problem among them such as surge in price or price instability of shallots that can trigger imports and it could be harmful to farmers. Wanasari sub-district is one of the shallots centers located in Brebes regency of Central Java, the last five years has decreased production. The purpose of this research is to know the effect of asset, land area, labor, seedlings, fertilizers, and pesticides factors against the level of production of shallots. The data in this study used primary and secondary data with samples of 70 farmers. The analysis method in this study was the multiple linear regressions.